Caregiver conception about child development with cerebral palsy after intervention physiotherapeutic (Research, Society and Development, 2021)
This article aims to understand the conception of caregivers of children with cerebral palsy about the interference of physical therapy treatment in their development. It adopts a descriptive character with a qualitative approach, developed at the School of Physiotherapy Clinic (CEF) of the State University of Southwest Bahia. The collection was carried out in the caregivers' homes and/or in the CEF itself. Caregivers of children with cerebral palsy (CP) aged 2 to 10 years, who attended physical therapy for at least 6 months, participated in this study. It was a semi-structured interview analyzed using Bardin's content analysis. The study complied with the decrees of Resolution 466/12 approved by the Plenary of the National Health Council. With the analysis of changes, categories emerged such as: the meaning of physical therapy for the caregiver, a child after physical therapy and how it would be if there was no treatment, caregiver participation in the treatment, a child enjoying physical therapy and the difficulties encountered in giving process to treatment. It was concluded that, for the most part, caregivers consider physical therapy treatment to be important for the development of their children.